KEPUASAN KONSUMEN DI INDUSTRI SUVENIR DALAM PERSPEKTIF E-COMMERCE DAN KUALITAS LAYANAN - Budi Prasetiyo (Universitas Nasional Pasim) (Jurnal Manajemen Industri dan Logistik (JMIL), 2021)
AbstractThis research was conducted on XYZ Souvenir consumers. The purpose of this research is to determine how much the contribution of the use of E-commerce and Service Quality affects customer satisfaction both partially and simultaneously on XYZ Souvenir.  The research method that will be used in this research is the verification method. In this research, the unit of analysis is individuals, namely XYZ Souvenir consumers. The sample in this study was 134 respondents. Systematic random sampling is a sampling withdrawal technique used in this study. The analysis method uses path analysis, while also testing the validity and reliability of the research instrument. Based on the results of the study indicate that there is an effect both partially and simultaneously on exogenous variables (E-commerce and Service Quality) on endogenous variables (customer satisfaction). The implication of this research that XYZ Souvenir can make various improvements a good site design (such as information on goods/services that are complete and clear, there are promotions such as giving discounts, and special offers, accepting proposals from consumers payment features used, making online promotions) and adding product variations.